MODEL STRUKTURAL PENINGKATAN LOYALITAS KONSUMEN PADA PRODUK UMKM MEREK BITTERSWEET BY NAJLA DI INDONESIA - Mochamad Nurhadi; Muchammad Ardafa Baihaqi; Arif Zeinfiki Djunaedi; Ali Soebijanto (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2024)
Social media is a digital platform that is widely used in the business world, especially by Micro, Small and Medium Enterprises (MSMEs). Bittersweet by Najla is an MSME product that utilizes social media to increase brand loyalty. The research objective is to analyze the increase in brand loyalty based on social media marketing activities, brand trust, brand equity, and brand attachment to Bittersweet by Najla brand MSME products in Indonesia. This study is categorized as causal research using a survey method. The sampling technique used purposive sampling with 227 respondents as the research sample. The analysis technique used is Partial Least Square with Structural Equation Modeling (PLS-SEM) using the SmartPLS application. The results of the study show that an increase in brand loyalty is not directly determined by social media marketing activities, but through the mediation of brand trust, brand attachment, and brand equity shows a significant increase in the relationship. The research results concluded that the increase in consumer loyalty for Bittersweet by Najla is significantly determined by the amount of brand trust, brand attachment, and brand equity.